PENERAPAN METODE PEMBELAJARAN SAVI (SOMATIS, AUDITORI, VISUAL DAN INTELEKTUAL) DALAM MENINGKATKAN HASIL BELAJAR DI SMPN 1 TURIKALE - Rahman, Maryam Khaerani; Ahmad; Sumardin, Andi; Mustamin; Syahrul, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement of student learning outcomes through the application of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning method in Islamic Religious Education subjects in class VIII G of SMP Negeri 1 Turikale, Maros Regency. The problem in this study is the low learning outcomes of students caused by the lack of student activity in the learning process and the use of learning methods that are still dominated by lecture methods. This study is a Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. The subjects of the study were 30 students of class VIII G of SMP Negeri 1 Turikale, Maros Regency. Data collection techniques were carried out through observation, learning outcome tests, and documentation. The data obtained were analyzed using quantitative and qualitative descriptive analysis techniques. The results of the study indicate that the application of the SAVI learning method can improve student learning outcomes in Islamic Religious Education subjects. This can be seen from the increase in the percentage of student learning completion in each cycle. In the pre-cycle stage, only 34% of students achieved learning mastery. After the implementation of the SAVI method in Cycle I, the percentage of mastery increased to 53.33%. Furthermore, in Cycle II, learning mastery increased significantly to 90%. In addition to improving learning outcomes, the SAVI method was also able to increase student activity, participation, motivation, and the ability to discuss and collaborate during the learning process. Based on the results of this study, it can be concluded that the implementation of the SAVI learning method (Somatic, Auditory, Visual, and Intellectual) is effective in improving the learning outcomes of Islamic Religious Education students in class VIII G of SMP Negeri 1 Turikale, Maros Regency.